2011
DOI: 10.1080/17511321.2011.602585
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Play With the Elements: Towards a Phenomenology of Risk Sports

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Breivik, G. (2011 Dangerous Play with the Elements -Towards a Phenomenology of Risk SportsGunnar Breivik, Norwegian School of Sport Sciences AbstractThe purpose of the article is to present a phenomenological description of how athletes in specific risk sports explore human interaction with natural elements. Skydivers play with, and surf on, the encountering air while falling towards the ground. The kayakers play on the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Nicols (2000) wrote that freedom defines "Dasein's authentic potentiality for being, a potentiality which reveals the being of beings as they are 'in themselves', including both innerworldly beings and Dasein itself" (p. 3). Freedom entails being free from the social "they" of everyday life and accepting the reality of the abyss (nothingness), the acceptance of the presence of anxiety and of being open to confront one's own death (Breivik, 2011).…”
Section: Phenomenology and Freedommentioning
confidence: 99%
“…Nicols (2000) wrote that freedom defines "Dasein's authentic potentiality for being, a potentiality which reveals the being of beings as they are 'in themselves', including both innerworldly beings and Dasein itself" (p. 3). Freedom entails being free from the social "they" of everyday life and accepting the reality of the abyss (nothingness), the acceptance of the presence of anxiety and of being open to confront one's own death (Breivik, 2011).…”
Section: Phenomenology and Freedommentioning
confidence: 99%
“…Dangerous sports put people from relatively safe societies into situations which highlight 'human finitude' as a fundamental component of authentic understanding (Martínková & Jim Parry 2016). Disruption of the everyday life world can provide a glimpse of authenticity (Breivik 2010(Breivik , 2011. Sartre already underscored the continuity between scientific research (the quest for knowledge) and skiing, and this seems to be confirmed by Turist, although skiing seems directed at deepening self-knowledge rather than nature knowledge.…”
Section: The Experimental Moviementioning
confidence: 66%
“…Besides the fact that several pictures of Heidegger on skies can be found on the Internet, it is well known that one of his key concepts, namely Die Kehre, Heidegger's famous 'turn' , is actually a skiing term, borrowed from the skiing vocabulary, Heidegger's preferred sport (Janicaud 2015, 242). Apparently, he was quite proficient in it, skiing all the way from his famous hut in Todtnauberg to the lecturing hall at the University of Freiburg (Breivik 2011;Moran 2000). The meaning of skiing may have changed dramatically during recent decades, however, so that nowadays skiing not only exemplifies forgetfulness of nature but also the inauthenticity of contemporary consumerist existence, with tourists buying commodified experiences and quality time (Pine and Gilmore 1999) instead of really exposing themselves to authentic ecstatic peak experiences of self-forgetfulness (Martínková 2011;Vannatta 2008).…”
mentioning
confidence: 99%
“…La práctica de modalidades deportivas en este, como canoa, kayak y rafting, es cada vez más popular entre los DA; sin embargo, se puede convertir en un ambiente hostil para los competidores y deportistas si las condiciones meteorológicas se muestran adversas (Breivik, 2011). Así, es posible observar la importancia que tiene el clima en la práctica de los DA, ya que sus condiciones variarán según la época del año.…”
Section: Introductionunclassified